Aplikasi Client Server Berbasis Android pada Barbershop The Barbega Menggunakan Model Multi Channel - Single Phase - Yurindra Yurindra; Ari Amir Alkodri; Anisah Anisah; Supardi supardi (ISB Atma Luhur, 2020)
A common problem that is often faced by almost most Barbershop is in terms of serving customer queues, for barbershops who have many customers and have many service chairs, then of course a good customer queue service management concept is needed as well. One of the concepts of queuing services for customers is how queue information can reach customers without queuing at the location. For this reason, a queue service concept for customers is needed based on Android. Android is preferred because almost all smartphone users are currently based on Android. The application will be built based on the concept of client server so that the queue service will occur in real time. The Queuing model used is Multi Channel Single Phase, because in the queue at barbershop there will only be one stage of the process, but it requires a lot of queue flow. This can be seen in the structure of the development diagram. By using an Android-based application based on a single phase multi channel model that will be built it is ensured that customers will find it helpful, without having to spend time in a queue customers can order queues and see queues in real time so they can rush to barbershop when it is close to the queue